Understanding Blended Finance: How different definitions of blended finance result in different inputs and outputs and what to expect - Al Anshori, Farahdina; Salomo, Roy Valiant; Kusumastuti, Retno (Technium Social Sciences Journal, 2023)
Several breakthroughs were made to achieve the SDGs targets, including in the development funding subject, namely blended finance. As a new approach to development financing, this approach is not yet widely understood. One of the basic problems is that there is no internationally agreed definition of what blended finance is. The actors translate this concept according to the characteristics of their respective institutions. This translation causes a variety of blended finance, from the types of input in the blended finance operation, what output is produced from the collaboration, to what impact these institutions expect from the blended finance project they are involved. This paper examines the definitions of blended finance from four institutions commonly involved in blended finance projects, i.e. OECD, DFI, Convergence, and the European Union. By reviewing a selection of reports and their working papers, it can be concluded that the input, output, and impact expected by these actors depend on the blended finance definition they make respectively. Actors whose definition focuses on development are more toward developmental impact, while actors whose definition focuses on an economic perspective prefer focusing on projects with profit-oriented impacts. Understanding the matter will help those new players in blended finance, including policymakers, to decide which partner is more suitable to collaborate in which phase of blended finance.